k look at this example, i shud be able to do this without substitution....
using (INT) 1/(a^2 + (f(x))^2 ) = 1/a arctan x/a
i can say that (int) 4/(x^2 -2x + 3)dx = 4(int) 1/(x-1)^2 +2 dx
there = 4/root2 arctan (x-1)/root2 + c
which is correct,, are you saying thatbecause with my previous example the
f(x) has a coefficient if you like of three before it i have to use substitution?
See my signature for LaTeX typesetting, really, see it to make your posts clearer.
(Bow)(Bow)(Bow)(Handshake) U HAVE TO SUBSTITUTE U=3X+1
DX=DU/3 CANCELS + GIVES ANSWER PRESUMABLY I MUST SUBSTITUTE WHENEVER THERE A COEFFICIENT OF X IN THOSE BRACKETS!?
Effectively, you could put it that way, yes, or you could just do it in your head =)